2021
DOI: 10.3389/fcvm.2021.741260
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Acute Myocarditis With Short-Term Outcomes and Factors for Extracorporeal Membrane Oxygenation: A Single-Center Retrospective Cohort Study in Vietnam

Abstract: Objective: Data on the management and outcomes of acute myocarditis treated with extracorporeal membrane oxygenation (ECMO) among low- and middle-income countries are limited. This study aimed to determine the short-term outcomes and also identify factors associated with ECMO use among children with acute myocarditis at a tertiary children's hospital in Vietnam.Methods: A single-center, retrospective observational study was conducted between January 2016 and February 2021. Pediatric patients with acute myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We further excluded 42 studies after full‐text evaluation, because they did not meet inclusion criteria. Eventually, 28 studies 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 were amenable to meta‐analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We further excluded 42 studies after full‐text evaluation, because they did not meet inclusion criteria. Eventually, 28 studies 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 were amenable to meta‐analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our meta‐analysis, applying a random‐effects model, the pooled short‐term mortality (28 studies,1736 patients) was 45.6% (95% CI, 38.7%–52.4%) (Figure 2 ). 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 There was no evidence for publication bias because of the funnel plot appearing visually symmetrical (Figure 3 ), and the Egger test suggesting insignificant difference for our primary outcome of interest ( P egger =0.23). The sensitivity analysis performed by excluding the studies with a Joanna Briggs Institute score <8, showed that the pooled short‐term mortality was 46.2% (95% CI, 39.0%–53.4%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations